AI Competence’s Impact on Innovation in The Creative Industries: Moderating Role of Individual Creativity - Pranandari, Rizka Putri; Aoyama, Atsushi (Universitas Airlangga, 2025)
This research aims to investigate the relationship between Artificial Intelligence (AI) competence and innovation, as well as the moderating effect of creativity in the context of Indonesian creative industries. The objectives are accomplished by conducting surveys and analyzing the data using a quantitative approach. The samples are people who are working in various sectors of the creative industries in Indonesia, with a minimum age of 18. The data was collected by using a non-probability, convenience sampling method. 268 completed questionnaires were collected from the eligible samples. The results of hypothesis testing using PLS-SEM indicate that AI competence has a significantly positive impact on innovation. While individual creativity moderates the relationship between AI competence and innovation. Intriguingly, this moderating effect goes in the negative direction. For the theoretical implication, the effect of creativity in enhancing competence, especially in using new technology, should be studied further by more rigorous research. In addition, this research suggests that the creative industries stakeholders should provide sufficient training for creative workers, allowing them to develop their competence in using AI programs related to their job or tasks.